2020
DOI: 10.2147/ott.s286627
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA MIR205HG Drives Esophageal Squamous Cell Carcinoma Progression by Regulating miR-214/SOX4 Axis

Abstract: Background Esophageal squamous cell carcinoma (ESCC) is a common and fatal malignancy, which has posed a great challenge to public health, especially in China. Dysregulation of long non-coding RNAs is involved in the occurrence, development, invasion, and metastasis of multiple cancers including ESCC. However, little is known about the function of MIR205HG in ESCC. Methods We used qRT-PCR to detect the expression level of MIR205HG, miR-214, and SOX4 in human ESCC tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…It is implicated that MIR205HG widely participates in diverse types of cancers. For example, Li et al have certified that MIR205HG aggravates the process of esophageal cell carcinoma through sponging miR-214 and regulating SOX4 expression ( 14 ). Liu et al have identified that MIR205HG acts as an oncogene in lung squamous cell carcinoma [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is implicated that MIR205HG widely participates in diverse types of cancers. For example, Li et al have certified that MIR205HG aggravates the process of esophageal cell carcinoma through sponging miR-214 and regulating SOX4 expression ( 14 ). Liu et al have identified that MIR205HG acts as an oncogene in lung squamous cell carcinoma [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a common lncRNA, MIR205HG has been also investigated in multiple malignancies, including esophageal cell carcinoma, lung squamous cell carcinoma, cervical cancer and so on [ 14 16 ]. In this study, we probed into the effects of MIR205HG on the progression of HB and investigated into the latent regulatory mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CHRM3.AS2 was a risk-associated gene in our study, which was highly expressed in CCA. Moreover, as for MIR205HG, Li et al demonstrated that MIR205HG could exert roles on cell cycle, migration, and apoptosis of esophageal squamous cell carcinoma by mediating miR-214 negatively and regulating SOX4 as a molecular sponge, which can be regarded as a novel candidate for the diagnosis and treatment of that tumor (40). In another recent study, Liu and colleagues demonstrated that by acting as a competing endogenous RNA, MIR205HG could accelerate lung squamous cell carcinoma development via mediating the molecular axis of miR-299-3p/MAP 3 K2 (41).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that MIR205HG functions as a fundamental player in various human cancer by affecting different pathways in a context-dependent manner [ 15 , 16 ]. In this work, the biological role of MIR205HG in OS was characterized.…”
Section: Introductionmentioning
confidence: 99%